Upaya Guru Meningkatkan Kecerdasan Emosional dan Spiritual Peserta Didik melalui Pembelajaran Akidah Akhlak di Madrasah Tsanawiyah Ma’arif Tieng - Akromah Akromah; Ngarifin Shidiq; Sri Haryanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to: 1) Determine the efforts of MTs Ma'arif Tieng teachers in improving students' emotional and spiritual intelligence through Akidah Akhlak learning, and 2) Determine the factors that encourage and inhibit the development of students' emotional and spiritual intelligence. The data collection for this research was carried out qualitatively through documentation, interviews, and observations. The data analysis techniques used were data reduction, descriptive presentation, and triangulation. Based on the results of the study, educators used discussion techniques, positive behavior patterns, role models, rewards, and punishments to help children develop their emotional and spiritual intelligence. Supporting factors include cooperation between teachers and homeroom teachers, student enthusiasm, and madrasah programs such as da'wah activities, tahfiz, duha prayer, reading of rotibul athos, and OSIS. Meanwhile, inhibiting factors include negative attitudes of students, lack of ability to read the Qur'an, and low learning discipline. This research is expected to add insight into the importance of the role of Akidah Akhlak teachers in improving students' spiritual and emotional intelligence, as well as encourage the development of more effective learning methods in this field.